Aerosol optical properties and brown carbon in Mexico City. Issue 3 (14th April 2022) - Retama, Armando; Ramos-Cerón, Mariana; Rivera-Hernández, Olivia; Allen, George; Velasco, Erik
Abstract : 65–74% of light extinction is due to light scattering in Mexico City. Organic aerosols dominate both submicron mass loading and light scattering. Brown carbon and black carbon contribute 22% and 78% to the total light absorption, respectively. Road traffic and regional wildfires are the main contributors to light absorption. The aerosols' optical properties exhibit distinctive diurnal and seasonal patterns. Abstract : Brown carbon (BrC) is a component of particulate matter which has significant impacts on climate forcing and air quality. To elucidate the current state and sources of BrC in Mexico City, the largest megacity in North America, the aerosols' ability to scatter and absorb light was evaluated over two years in concert with detailed chemical speciation of their components during a period of six months. These measurements made it possible to evaluate the seasonal and diurnal variations of the chemical composition, optical properties, and origin of BrC. It was found that 67% of the light extinction at 870 nm is due to scattering. Organic aerosols dominate the submicron mass loading (62%), as well as the light scattering (>50%). Nitrate and sulfate compounds are also important contributors to light scattering. Among the organic fraction, fresh particles strongly associated with traffic emissions dominate the light absorption at ultraviolet (UV) wavelengths on days not affected by biomass burning plumes. Regional wildfires are ubiquitous in the central region of Mexico during the dry-warm season (March–May) and can drastically increase the light scattering and absorption attributed to the organic fraction. During wildfire episodes, the organic fraction can contribute up to 80% and 50% to light scattering and absorption, respectively. Aged organic aerosols have a negligible contribution to light absorption at UV wavelengths, but secondary organic aerosols of recent formation contribute on average 24% in days not affected by wildfire plumes. Brown carbon and black carbon (BC) contributed 22% and 78% to the total light absorption in México City, respectively. Brown carbon increases on average 28% the light absorption over that attributed to BC. This increase can be up to 32% during the dry-warm season. In summary, vehicular traffic is the main contributor to BrC light absorption on a daily basis, while biomass burning becomes the major contributor during wildfire episodes.